Ecology of childhood: the problem of imagination development of younger schoolchildren - Chorna, Olena (Personality and environmental issues, 2023)
The article emphasizes the need to develop the imagination of younger schoolchildren as an important factor in the formation of their creative personality. It is emphasized that primary school age is a sensitive period for the development of imagination, and therefore the task of a modern primary school is to use a period favorable for the development of this mental function.The role of the teacher in the development of students' imagination is revealed. It is emphasized that the main priority in the educational process of primary school should be to ensure proper childhood ecology. The teacher needs to organize the educational process so that it is environmentally friendly for children. The teacher's task is to preserve the creative tendency of the preschool age, to strengthen it in the younger school age, in other words, to preserve the creative potential of the child in new conditions where abstract, conceptual, theoretical knowledge prevails.It was found that in order to ensure the activation and effective course of the imagination development process in younger schoolchildren, it is necessary for the teacher to create and observe the following psychological and pedagogical conditions: possession of scientific knowledge and technological skills regarding the development of imagination of students; taking into account the age, gender and individual psychological characteristics of the development of imagination of younger schoolchildren; ensuring a favorable psychological atmosphere in the course of extracurricular and extracurricular educational activities; creation of a creatively developing educational environment, as well as organization of joint creative activities with students; building educational and educational interaction with students on the basis of a dialogical approach; the use of a system of creative tasks, innovative technologies for the development of imagination; promoting the manifestation and realization of students' interests and abilities by involving them in various types of creative activities.